Pengaruh Pertumbuhan Penduduk Terhadap Ketersediaan Lapangan Kerja Di Kabupaten Sidenreng Rappang - Rohani Rohani (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Abstract The goal of this research was to determine how people’s fertility level affected chances to get a job in Sidenreng Rappang region along with all influencing factors. This descriptive type of research tried to describe the effect of people’s fertility level to chances to get a job in Sidenreng Rappang region, based on quantitative research. Collecting the data used observation, interview by questionnaire to some chosen people. The samples were taken using proportionate stratified random sampling within all work-capable people population in Sidenreng Rappang region. The results showed that people’s fertility level scored 3,53% (quite affective), so generally Sidenreng Rappang people had the assumption that their fertility level did affect job chances. This results came from the summary of affecting factors, which are: (1) Fertility level did affect people’s job chances from calculation 942:270 = 3,4 (quite affective). (2) The effect of mortality level to job chances was 996:270 = 3,68 (quite affective). (3) The effect of people’s migration to job chances was done by combining the score and frequency, 948:270 = 3,51, which indeed was quite affective.